Effect of pre-treatments on drying characteristics of Chinese jujube (Zizyphus jujuba Miller) - Baomeng, Zhu; Xuesen, Wen; Guodong, Wei (International Journal of Agricultural and Biological Engineering, 2014)
Chinese jujube is delicious and nourishing fruit. However, fresh Chinese jujube is liable to rot and drying is a necessary process. Traditional drying is a time-consuming task due to the thick cuticle of Chinese jujube. To improve its drying efficiency, fresh Chinese jujube was pretreated with nine different methods prior to hot-air drying. Among these methods, dipping in 2% ethyl oleate plus 5% K2CO3 for 10 min (alkaline emulsion of ethyl oleate, AEEO) was recommended for its time-saving effect, which was found more significant at lower drying temperatures. The beneficial effect was considered based on its cuticle destruction by AEEO pre-treatment. In the meantime, the drying process was divided into three stages; each of them obeyed the first order reaction kinetics. Activation energies for the first, second and third stages of control over jujube drying were 41.45 kJ/mol, 35.24 kJ/mol and 49.52 kJ/mol, and reduced by 20.9%, 22.1% and 29.0%, respectively, after AEEO pre-treatment, and the drying process was well predicted by Midilli et al. model. In view of browning during drying at higher temperatures, AEEO pretreated jujube was suggested to be dried at 60°C. This finding was considered to be helpful to the industrial drying of Chinese jujube.